Tackling the Challenge of Packaging Plastic in the Environment. Issue 35 (5th June 2020) - Norton, Michael
Abstract : How to solve a problem like man‐made plastics? In this Science Voices article, Dr. Michael Norton, Programme Director of the European Academies Science Advisory Council (EASAC) summarizes a recent report on the challenges and progresses concerning plastics in the environment.